ANALISIS RISIKO KERUSAKAN PADA MESIN PEMBUAT PELET IKAN LELE - Ramasandi Rifan Yogiantoro; Dianta Mustofa Kamal (Jurnal Mema (Jurnal Mesin dan Manufaktur), 2025)
This study aims to analyze the potential risk of failure in a horizontal-type catfish pellet-making machine using the Failure Mode and Effect Analysis (FMEA) method. The analysis is conducted theoretically based on machine design principles, material characteristics, and operational load. The approach aims to evaluate design weak points, identify potential failure modes, and propose recommendations for improving component reliability. The main components analyzed include the driving motor, gearbox, screw shaft, cutting blade, heater, and frame. Results indicate that the screw shaft and driving motor have the highest Risk Priority Number (RPN) values, indicating potential failures due to excessive torque load and unstable thermal conditions. Design improvements are recommended, including the use of wear-resistant materials such as AISI 4140 steel, improved motor cooling systems, and optimized screw geometry. The findings are expected to contribute to the development of more reliable and efficient pellet-making machine designs.